New and future developments in microbial biotechnology and bioengineering penicillum System Properties and Applications - Gupta, Vijai Kumar; Rodriguez-Couto, Susana (Elsevier, 2017)
New and Future Developments in Microbial Biotechnology and Bioengineering: Penicillium System Properties and Applications covers important research work on the applications of penicillium from specialists from an international perspective. The book compiles advancements and ongoing processes in the penicillium system, along with updated information on the possibilities for future developments. All chapters are derived from current peer reviewed literature as accepted by the international scientific community. These important fungi were found to secrete a range of novel enzymes and other useful proteins, and are still being extensively studied and improved for specific use in the food, textile, pulp and paper, biocellulosic ethanol production and other industries. The book caters to the needs of researchers/academicians dealing with penicillium spp. related research and applications, outlining emerging issues on recent advancements made in the area of research and its applications in bioprocess technology, chemical engineering, molecular taxonomy, biofuels/bioenergy research and alternative fuel development. In addition, the book also describes the identification of useful compound combinations/enzyme cocktails and the fermentation conditions required to obtain them at an industrial scale. Finally, the book provides updated information on the best utilization of these fungi as a natural tool to meet the next challenges of biotechnology.--Provided by publisher.